2007
DOI: 10.1038/sj.jcbfm.9600571
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cerebral Fluoro-l-Dopamine Uptake in Adult Patients Suffering from Phenylketonuria

Abstract: Deficiency of phenylalanine hydroxylase activity in phenylketonuria (PKU) causes an excess of phenylalanine (Phe) throughout the body, predicting impaired synthesis of catecholamines in the brain. To test this hypothesis, we used positron emission tomography (PET) to measure the utilization of 6-[ 18 F]fluoro-L-dopamine (FDOPA) in the brain of adult patients suffering from PKU and in healthy controls. Dynamic 2-h long FDOPA emission recordings were obtained in seven adult PKU patients (five females, two males;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…The specific mechanism leading to the presence of these ADHD symptoms in persons with PKU is currently unknown; however, it may be caused by a direct toxic effect of phenylalanine levels. It has also been suggested that reduced tyrosine levels in PKU may decrease dopamine and norepinephrine production in the central nervous system [24,25,49,50]. Results of this clinical trial population showed a correlation between serum phenylalanine levels and inattention scores in sapropterin responders and has been discussed in the primary publication [27], but in the pooled population of responders and nonresponders, this correlation was weak.…”
Section: Discussionmentioning
confidence: 79%
“…The specific mechanism leading to the presence of these ADHD symptoms in persons with PKU is currently unknown; however, it may be caused by a direct toxic effect of phenylalanine levels. It has also been suggested that reduced tyrosine levels in PKU may decrease dopamine and norepinephrine production in the central nervous system [24,25,49,50]. Results of this clinical trial population showed a correlation between serum phenylalanine levels and inattention scores in sapropterin responders and has been discussed in the primary publication [27], but in the pooled population of responders and nonresponders, this correlation was weak.…”
Section: Discussionmentioning
confidence: 79%
“…Because Phe shares a common transport system across the blood brain barrier with tyrosine and tryptophan, elevated Phe levels also limit the entry of these amino acids into the central nervous system (Pardridge & Choi, 1986). As precursors to the neurotransmitters dopamine/ neuroepinephrine and serotonin, low tyrosine and tryptophan levels, respectfully, in the CNS can impact the critical regulation of mood, anxiety, and cognition provided by these neurotransmitters (Burlina, Bonafé, Ferrari, Suppiej, & Zacchello, 2000;Landvogt et al, 2008;Stahl, 2000). This dynamic phenomenon involving concurrent Phe has the potential to affect adults with early-and late/untreated PKU and may subsequently contribute to improvements associated with Phe reduction in either group that relate to mood, anxiety, behavior, and functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The logistical challenge of this set-up reduced the number of subjects willing to participate. Thus, 6 out of the previously reported 10, 11 16 patients underwent MRS scanning in addition to PET scanning. One may wonder whether plasma concentrations of LNAAs, in particular of Phe, remained stable throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, two clinical radioisotope studies support an inhibitory effect of elevated plasma Phe concentrations on blood-to-brain transport of non-Phe LNAAs in PKU patients. 16,21 Specifically, elevated plasma Phe concentrations were shown to reduce uptake of 75 Se-selenomethionine 21 and were associated with reduced apparent blood-to-brain transport of 6-[ 18 F]-L-dihydroxyphenylalanine, 16 a substance which, like the LNAAs, is transported across the BBB by the LNAA type-I transporter.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation